Does the addition of proteases affect the biogas yield from organic material in anaerobic digestion?. (March 2016) - Müller, Liane; Kretzschmar, Jörg; Pröter, Jürgen; Liebetrau, Jan; Nelles, Michael; Scholwin, Frank
Highlights: Enzymes showed different effects in batch tests and semi-continuous biogas tests. Tenfold concentrated proteases resulted in increased biogas production in batch tests. No positive effect of proteases was shown in semi-continuous biogas tests. Phenylacetate and -propionate increased before VFA or VOA. Abstract: The aim of this study was to investigate the biochemical disintegration effect of hydrolytic enzymes in lab scale experiments. Influences of enzyme addition on the biogas yield as well as effects on the process stability were examined. The addition of proteases occurred with low and high dosages in batch and semi-continuous biogas tests. The feed mixture consisted of maize silage, chicken dung and cow manure. Only very high concentrated enzymes caused an increase in biogas production in batch experiments. In semi-continuous biogas tests no positive long-term effects (100 days) were observed. Higher enzyme-dosage led to a reduced biogas-yield (13% and 36% lower than the reference). Phenylacetate and -propionate increased (up to 372 mg l −1 ) before the other volatile fatty acids did. Volatile organic acids rose up to 6.8 g l −1 . The anaerobic digestion process was inhibited.